O PROCESSO DE DESESTRUTURAÇÃO E DISSOLUÇÃO DO FAXINAL DA CONCEIÇÃO – REBOUÇAS/PR (1950 – 2018) - Silva, Fabio Marcelo Andrade (2019)
This present work aims to investigate and understand how the process of desorganização and dissolução of Faxinal da Conceição, which lost its main characteristics (animal community breeding) in the 1980s, happened, highlighting landscape elements that experienced alterations after this process. This work discuss about Povos Tradicionais, specifically the Faxinalenses, whose main characteristic is the collective use of natural resources, mainly for animal breeding. Another important feature of Povos Tradicionais is that their animals are bred on the loose. As a source to this research, interviews and photographs were used, for the purpose of highlight some of the changes due to the process of desintegração and dissolução that Faxinal has suffered. This process is associated with a progress speech and the effects of technology arrival, therefore, wire fences, monoculture of soybeans, beans and corn had appeared, causing a reduction of the native forest. The time chosen in this work was delimited between the years of 1950 and 2018. Photographs from the 1950s and also current pictures were used in order to understand the differences resulting from the historical movement that happened when Gaúcho migrant arrived in Faxinal da Conceição.